P-020 The use of HF-OCT in the prediction of aneurysm occlusion. (22nd July 2019) - King, R; Marosfoi, M; Caroff, J; Ughi, G; Groth, D; Gounis, M; Puri, A
Abstract : Introduction: The development of High Frequency OCT 1 (HF-OCT) allows for higher resolution intra-arterial imaging, such that vascular remodeling in response to stents and next generation intrasaccular devices (NGID) can be interrogated. We hypothesize that imperfections or gaps in the neck coverage of an aneurysm after treatment with a NGID will be predictive of failed aneurysm occlusion. Materials and methods: Two aneurysms were made in each of six dogs, one sidewall aneurysm on the distal right common carotid artery (CCA), and a bifurcation aneurysm proximally at the apex of an anastomosis between the left and right CCAs. One aneurysm was excluded due to thrombosis at the time of treatment. Each aneurysm was treated with either detachable coils, or NGID, with a 7:4 randomization NGID:COIL. At implant, HF-OCT was obtained after each aneurysm was successfully packed. At 180 days, animals were assessed for final aneurysm occlusion by DSA. Separately, the HF-OCT data sets were automatically segmented such that gaps in the coverage of the aneurysm neck could be identified and used to predict if the aneurysm occlusion at 180 days. Results: The overall rate of occlusion was not seen to be different between the NGID and COIL group (p=0.45) on the Raymond-Roy scale. 2 All of the NGID constructs were successfully segmented, and the associated larges gap in the neck coverage for each was determined. A gap in the NGID construct at the level of the neck greater than 1 mm 2 predicted failed aneurysm occlusion at 180-days (p = 0.047). This threshold correctly classified all aneurysms. Conclusions: HF-OCT allows not only for the imaging and segmentation of intra-arterial devices in vivo, but showed great potential as a robust diagnostic tool. Preliminary evidence collected in this study showed that HF-OCT can prognosticate aneurysm treatment success at the time of treatment. References: Stroke. 2018:Nov29:STROKEAHA118022315 Stroke . 2003;34(6):1398–1403. Disclosures: R. King: None. M. Marosfoi: None. J. Caroff: None. G. Ughi: 4; C; Gentuity LLC. 5; C; Gentuity LLC. D. Groth: None. M. Gounis: None. A. Puri: None.